2005
DOI: 10.1152/ajpheart.00938.2004
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin expression and activity during coronary collateralization

Abstract: Coronary collateral development relies on the coordinated secretion of growth factors. However, alone they are insufficient for permanent collateral growth. We utilized proteomics to identify other important proteins in the extracellular environment that could facilitate collateralization. Chronically instrumented dogs developed coronary collaterals by the repetitive occlusion method. Subendocardial (0.19 Ϯ 0.04, 0.27 Ϯ 0.06, 0.48 Ϯ 0.10, and 0.81 Ϯ 0.11 ml ⅐ min Ϫ1 ⅐ g Ϫ1 on days 1, 7, 14, and 21, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Schalkwijk et al detected raised A1GP levels in patients with indirect signs of endothelial activation [32]. Involvement of iron metabolism in conditioning endothelial function has been documented [33] and an APP acting on iron levels such as HG has been reported as connected with development of collateral coronary flow [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…Schalkwijk et al detected raised A1GP levels in patients with indirect signs of endothelial activation [32]. Involvement of iron metabolism in conditioning endothelial function has been documented [33] and an APP acting on iron levels such as HG has been reported as connected with development of collateral coronary flow [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, pools representing 3 consecutive days of collection of iMIF or sMIF, termed "MIF collection pools," were used to supplement RPMI/B27 at a concentration of 10% vol/vol, the level of which was selected based on previous experiments evaluating the effects of iMIF on vascular cell lines (36). Most experiments used the following MIF collection pools: days 1-3, 7-9, 13-15, and 22-24. The selection of these pools was based on findings from previous studies (22,23,36).…”
Section: Resultsmentioning
confidence: 99%
“…iMIF was collected over 24 consecutive days by injecting 4 ml lactated Ringer solution into the catheter while simultaneously harvesting 4 ml MIF from the effluent end. It is estimated that this procedure causes a 20-fold dilution of the iMIF as calculated from the catheter volume (22). A control sham-operated dog that was identically instrumented was not occluded; sham-operated MIF (sMIF) was collected in parallel with iMIF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our own preliminary data in patients suggest that polymorphisms of the tumor necrosis factor-alpha promotor region are related to the extent of collateral circulation as visible by angiography. Interestingly, a study in dogs revealed that upregulation of the acute phase protein haptoglobin in the myocardial interstitial fluid could stimulate migration of vascular smooth muscle cells and collateral formation [34]. Earlier, Hochberg et al had suggested haptoglobin 2-2 in diabetics [35] as a genetic determinant of the extent of coronary collaterals.…”
Section: Genetic Determinantsmentioning
confidence: 99%